1978
DOI: 10.1111/j.1365-2605.1978.tb00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermine and Citric Acid in Human Prostatic Fluid

Abstract: Concentration of spermine (87 ± 13 μM) and citric acid (45 ± 4 mM) in prostatic fluids from 44 men were highly significantly correlated (r = 0.795). It was concluded that both probably arise from the same exocrine cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In spite of these published observations, there is a paucity of studies on the effects of vasectomy on accessory sex gland func¬ tion in the human male. Furthermore, a critical analysis of the world literature revealed that, in the majority of human studies, glandular function was monitored by examining the concentrations of secretory products in the ejaculate (Grégoire & Moran, 1972, 1973Kothari et al, 1977;Barkan et al, 1978;Nikkanen, 1978;Mendiratta et al, 1980;Naik et al, 1980;Bendvold et al, 1985;Parrish et al, 1987). Seminai plasma is a complex mixture of the products of several glands and it may therefore be more correct to compare glandular function on the basis of their total contributions to the ejaculate.…”
Section: Introductionmentioning
confidence: 98%
“…In spite of these published observations, there is a paucity of studies on the effects of vasectomy on accessory sex gland func¬ tion in the human male. Furthermore, a critical analysis of the world literature revealed that, in the majority of human studies, glandular function was monitored by examining the concentrations of secretory products in the ejaculate (Grégoire & Moran, 1972, 1973Kothari et al, 1977;Barkan et al, 1978;Nikkanen, 1978;Mendiratta et al, 1980;Naik et al, 1980;Bendvold et al, 1985;Parrish et al, 1987). Seminai plasma is a complex mixture of the products of several glands and it may therefore be more correct to compare glandular function on the basis of their total contributions to the ejaculate.…”
Section: Introductionmentioning
confidence: 98%
“…Fructose is the main substance secreted by the seminal vesicles and it is of paramount importance for the glycolitic metabolism of spermatozoa as they possess minimal storage of glycogen and thus depend on vesicular fructose [22]. Citric acid is mainly of prostatic origin and its increase in the ejaculate is always dependent on an androgen-stimulated elevation of prostate metabolism [23]. Citric acid has an important role in redox reactions of the glucides metabolism; moreover it activates prostatic acid phosphatase.…”
Section: Discussionmentioning
confidence: 99%